O PESSOAL É POLÍTICO: as estratégias político-comunicativas da mobilização #ExposedCG - ARIADNA THALIA ZORTEA BRAZ (2023)
This research investigates political-communicative strategies to encourage the participation of women reporting sexual violence in mobilizations aimed at sharing experiences on the internet, as well as the potentialities and limitations of social networking sites as means of empowerment for contemporary feminisms. Based on a feminist epistemological basis (SAFFIOTI, 2011; BIROLI, 2014; ARAÚJO, 2018; BOGADO, 2018; COSTA, 2018; AKOTIRENE, 2019; BANDEIRA, 2019; CARNEIRO, 2019; hooks, 2019; LUGONES, 2019; COLLINS, BILGE , 2021; GONZALEZ, 2022), the present work contributes to the mapping of aspects present in manifestations on Twitter that favor adherence and that can be used for the formulation of new campaigns aimed at confronting violence against women, considering the different social markers that affect the experience of these mobilizers. To this end, we raised 1,705 tweets indexed to #ExposedCG on June 1st and 2nd, when the hashtag reached the platform's Trending Topics. That said, using intersectionality as a critical praxis, in addition to Content Analysis (CA) techniques complemented with in-depth semi-structured interviews with two mobilizers, we verified the importance of building narratives in the face of oppression and violence that cross the experiences of different women and the construction of political solidarity, in order to politicize issues previously linked to the private sphere, and we list nine suggestions that corroborate the development of an activist culture with regard to the creation of mobilizations with a feminist perspective through social networking sites